Overview of Fraud Dynamics in Government: Trends, Causes, and Mitigation Strategies - Kohar, Yansen Pratama; Darmawati; HS, Rahmawati (Jurnal Economic Resource, 2024)
Fraud in government is a major challenge that impacts public trust and the efficiency of state administration. This study aims to analyze the trends, causes, and mitigation strategies of fraud in the government sector through a systematic literature review approach. Based on the fraud triangle theory which includes pressure, opportunity, and rationalization, it was found that fraud in the public sector is often triggered by weak internal control, political and economic pressure, and an organizational culture that is permissive of corruption. Recent trends show an increase in the use of digital technology in fraud modes, especially in data manipulation and public procurement. This study also identifies mitigation strategies, including the implementation of effective internal control, strengthening transparency, ethics education, and collaboration between supervisory institutions. These findings are expected to provide relevant policy recommendations for the government to improve transparency, accountability, and integrity in the public sector.